2006
DOI: 10.1002/macp.200600399
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of Poly(ε‐caprolactone) Networks with Modulated Water Uptake

Abstract: Summary: A PCL macromonomer was obtained by the reaction of PCL diol with methacrylic anhydride. The effective incorporation of the polymerizable end groups was assessed by FT‐IR and 1H NMR spectroscopy. PCL networks were then prepared by photopolymerization of the PCL macromonomer. Furthermore, the macromonomer was copolymerized with HEA, with the aim of tailoring the hydrophilicity of the system. A set of hydrophilic semicrystalline copolymer networks were obtained. The phase microstructure of the new system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 14 publications
2
27
0
6
Order By: Relevance
“…In Ref. [16] it was shown that PCL blocks in PCL-PHEA copolymer networks keep a certain capacity to crystallize as shown by DSC studies. Nevertheless, the behavior of PLLA-PHEA system is not the same.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In Ref. [16] it was shown that PCL blocks in PCL-PHEA copolymer networks keep a certain capacity to crystallize as shown by DSC studies. Nevertheless, the behavior of PLLA-PHEA system is not the same.…”
Section: Resultsmentioning
confidence: 99%
“…Co-polymerization is a usual strategy to decrease the crystallinity since the regularity required for crystalline order is disrupted by the presence of different monomeric units randomly distributed along the polymer chain. If the co-monomer is hydrophilic, as in the case with hydroxyethyl acrylate, the water absorption increases, facilitating water access to the polymer chains [16,20,26,27].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A few years ago, our group reported a new strategy for crosslinking and obtaining a hydrophilic polycaprolactone [16]. A PCL macromer was synthesized through the reaction of PCL diol with methacrylic anhydride in order to obtain methacrylate end capped PCL.…”
Section: Introductionmentioning
confidence: 99%